Evaluasi Efektivitas Media Komunikasi Dalam Pengelolaan Pegawai Tugas Belajar di Lingkungan Direktorat Jenderal Pajak - Aulia, Irfan Noviandy; Irwansyah, Irwansyah (Jurnal Visi Komunikasi, 2023)
The online communication media used by the directorate general of taxation to facilitate the need for communication facilities between graduates of the study assignment program and the admin is by using whatsapp and telegram platform. the purpose of this research is to find out and analyze the effectiveness of telegrams as a medium of information in solving administrative management problems for graduates of study assignment program within the directorate general of taxation. The concept used in this research is to compare the level of effectiveness of whatsapp and telegram in the management of graduates of the study assignment program within the Directorate General of Taxes using a mixed methods approach, namely a research method that combines quantitative research methods with explanatory evaluation survey methods and qualitative research methods with a qualitative research approach. phenomenology. the results of the study stated that telegrams were still unfamiliar and rarely used by employees (Table 4.1) The study assignment module on Telegram has been accessed and provides the information needed by study assignment employees (Table 4.2) , then based on the results of other studies where telegrams are quitely helpful as a center of media information for employees. The Suggestions for this research is to carry out socialization regarding the use of telegram as a means of communication between graduates of the study assignment program and admins within the Directorate General of Taxes.